Mathematical Computing of Coniferous Tree Ignition by the Cloud-to-Ground Lightning Discharge using Joule-Lenz's Law; International Journal of Electrical and Computer Engineering; Vol. 7, No. 3 - Baranovskiy N. V. Nikolay Viktorovich (2017, 2017)
Title screen